Outcomes of the Treatment with Glecaprevir/Pibrentasvir following heart transplantation utilizing hepatitis C viremic donors. Issue 9 (10th August 2020) - Reyentovich, Alex; Gidea, Claudia G.; Smith, Deane; Lonze, Bonnie; Kon, Zachary; Fargnoli, Anthony; Pavone, Jennifer; Rao, Shaline; Saraon, Tajinderpal; Lewis, Tyler; Qian, Yingzhi; Jacobson, Ira; et al.
Abstract: Background: The use of direct‐acting antivirals (DAA) has expanded transplantation from hepatitis C viremic donors (HCV‐VIR). Our team has conducted an open‐label, prospective trial to assess outcomes transplanting HCV viremic hearts. Glecaprevir/pibrentasvir (GLE/PIB) was our sole DAA. Methods: Serial quantitative hepatitis C virus (HCV) RNA PCR was obtained to assess HCV viral titers. Between January 2018 and June 2019, a total of 50 recipients were transplanted. Of these, 22/50 (44%) were from HCV‐VIR, the remaining 28 from non‐viremic (HCV NON‐VIR) donors. An 8‐week course of GLE/PIB was initiated at 1 week post‐transplant. Results: There was no difference in demographic or clinical parameters between groups. All 22 recipients of HCV‐VIR transplants became viremic. GLE/PIB was effective in decreasing viremia to undetectable levels by 6 weeks post‐transplant in all patients. The median time to first undetectable HCV quantitative PCR was (4.3 weeks, IQR: 4‐5.7 weeks). All patients demonstrated sustained undetectable viral load through 1‐year follow‐up. There was no difference in survival at one year between HCV NON‐VIR 28/28: (100%) vs HCV‐VIR 21/22 (95%) recipients. Conclusions: Our center reports excellent outcomes in transplanting utilizing hearts from HCV‐VIR donors. No effect on survival or co‐morbidity was found. An 8‐week GLE/PIB course was safe and effective when initiated approximately 1 week post‐transplant.